Comparison of gait between healthy participants and persons with spinal cord injury when using the advanced reciprocating gait orthosis. (April 2016) - Arazpour, Mokhtar; Joghtaei, Mahmoud; Bahramizadeh, Mahmood; Ahmadi Bani, Monireh; Hutchins, Stephen W; Curran, Sarah; Mousavi, Mohammad E; Sharifi, Guive; Mardani, Mohammad A
Background: The advanced reciprocating gait orthosis (ARGO) has a rigid structure which provides restricted movement at the hip, knee, and ankle joints and incorporates a pelvic section with an extended section in the lumbar region. Healthy subjects, when walking with an RGO in situ, could feasibly demonstrate the level of limitation in movement imposed by ARGO-assisted ambulation. Objective: The aim of this study was to compare the function of the advanced reciprocating gait orthosis when fitted with the dorsiflexion-assist ankle–foot orthoses on temporal–spatial parameters and kinematics of walking in both able-bodied people and those with spinal cord injury. Study design: Quasi experimental design. Methods: Data were acquired from six able-bodied and four spinal cord injury subjects who used an advanced reciprocating gait orthosis which incorporated dorsiflexion-assist ankle–foot orthoses. Kinematics and temporal–spatial parameters were calculated and compared. Results: All able-bodied individuals walked with speeds which were only approximately one-third that of when walking without an orthosis. The mean step length and cadence were both reduced by 48% and 6%, respectively. There were significant differences in hip, knee, and ankle joint range of motions between normal walking and walking with the advanced reciprocating gait orthosis both in able-bodied subjects and patients with spinal cord injury. There were also significant differences in the speed of walking, cadence, step length, hip range of motion, and ankle range of motion when using the advanced reciprocating gait orthosis between the two groups. Conclusion: Temporal–spatial parameters and lower limb sagittal plane kinematics of walking were altered compared to normal walking, especially when spinal cord injury subjects walked with the advanced reciprocating gait orthosis compared to the able-bodied subjects. Clinical relevance: To produce an improvement in RGO function, an increase in walking performance should involve attention to improvement of hip, knee, and ankle joint kinematics, which differs significantly from normal walking.